2019
DOI: 10.26508/lsa.201900352
|View full text |Cite
|
Sign up to set email alerts
|

PKAc is not required for the preerythrocytic stages ofPlasmodium berghei

Abstract: Plasmodium sporozoites invade hepatocytes to initiate infection in the mammalian host. In the infected hepatocytes, sporozoites undergo rapid expansion and differentiation, resulting in the formation and release of thousands of invasive merozoites into the bloodstream. Both sporozoites and merozoites invade their host cells by activation of a signaling cascade followed by discharge of micronemal content. cAMP-dependent protein kinase catalytic subunit (PKAc)–mediated signaling plays an important role in merozo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…A similar pathway may operate in Plasmodium sporozoites, where a shift from low to high K+ is associated with decreased CT activity, possibly reflecting the downregulation of microneme secretion (Kumar et al, 2007). Using the Flp/FRT‐based conditional mutagenesis system (Carvalho et al, 2004), Choudhary et al reported that the catalytic subunit of PKA (PKAc) is not required for sporozoite motility and hepatocyte infection (Choudhary et al, 2019). However, incomplete PKA depletion due to protein carryover cannot be ruled out, as was observed for PKG using the same genetic system (Falae et al, 2010; Govindasamy et al, 2016).…”
Section: Signal Transduction In Plasmodium Sporozoites During Migration and Invasionmentioning
confidence: 99%
“…A similar pathway may operate in Plasmodium sporozoites, where a shift from low to high K+ is associated with decreased CT activity, possibly reflecting the downregulation of microneme secretion (Kumar et al, 2007). Using the Flp/FRT‐based conditional mutagenesis system (Carvalho et al, 2004), Choudhary et al reported that the catalytic subunit of PKA (PKAc) is not required for sporozoite motility and hepatocyte infection (Choudhary et al, 2019). However, incomplete PKA depletion due to protein carryover cannot be ruled out, as was observed for PKG using the same genetic system (Falae et al, 2010; Govindasamy et al, 2016).…”
Section: Signal Transduction In Plasmodium Sporozoites During Migration and Invasionmentioning
confidence: 99%
“…Western blotting was performed as described previously (Choudhary, Gupta, & Mishra, 2019). Briefly, salivary gland sporozoites and schizonts were obtained as described above and total cell lysates were prepared in SDS sample buffer.…”
Section: Western Blottingmentioning
confidence: 99%
“…The amplified product was cloned into the pCR 2.1-TOPO vector. For the normalization of transcripts, Hsp70 was used (Choudhary et al , 2019). Total RNA was isolated from blood stage schizonts (Schz), liver stages (LS), midgut (MG), and salivary gland (SG) sporozoites using TRIzol reagent (Takara Bio, Japan) and an RNA isolation kit (Genetix, India) following the manufacturers’ instructions.…”
Section: Methodsmentioning
confidence: 99%